Effects of age and weaning conditions on blood indicators of oxidative status in pigs. - Arnaud Buchet; Catherine Belloc; Mily Leblanc-Maridor; Elodie Merlot (PLoS ONE, 2017)
Weaning is a source of social, nutritional and environmental disorders that challenge piglet health. This study assesses the relevance of using plasma indicators of oxidative status as biomarkers of health around weaning in pigs. Blood antioxidant potential (BAP), hydroperoxides (HPO), oxidative stress index (OSI, e.g. HPO/BAP), vitamin A and E concentrations were investigated in two different trials. Trial A was carried out in an experimental unit to investigate the effects of age (from 12 to 147 days of age), weaning (at 21 or 28 days of age) and management at weaning (in optimal (OC) or deteriorated (DC) conditions) on those parameters. Trial B was performed in 16 commercial pig farms to describe the variability of these indicators on field between 26 and 75 days of age. In trial A, between 12 and 147 days of age, HPO globally increased (P < 0.001), vitamin E concentration decreased (P < 0.001) whereas BAP and vitamin A concentration remained relatively stable (P > 0.1). Vitamins E and A concentrations dropped 5 days after weaning independently of weaning age, weaning conditions and expression of diarrhea (P < 0.001). Twelve days after weaning, whatever the weaning age, HPO and OSI increased in DC compared to OC piglets (P = 0.05 and P < 0.01) and in piglets exhibiting diarrhea compared to those without diarrhea (P < 0.01 and P < 0.001). In DC pigs, BAP was also decreased (P < 0.05) 12 days after weaning. On trial B, plasma concentrations of vitamins A and E decreased and HPO increased 5 and 19 days respectively after weaning (P < 0,001). Contrarily to trial A, BAP values did not drop after weaning. Piglets which had the lowest ADG (Average Daily Gain) after weaning had greater HPO and OSI and lower vitamin A and E concentrations after weaning but also lower vitamin E concentration before weaning (P < 0.05). In conclusion, HPO or OSI seem to be good indicators of health disorders around weaning and plasma concentration of vitamin E before weaning is associated to growth after weaning.